Embroidery manufacturing techniques for textile dipole antenna applied to wireless body area network. Issue 8 (April 2019) - Gil, Ignacio; Fernández-García, Raul; Tornero, José Antonio
This paper addresses the design, simulation, manufacturing, and experimental test of textile dipole antennas based on advanced embroidery techniques. The proposed dipoles are intended to operate at the 2.45 GHz industrial scientific and medical radio band for wireless body area network applications. Two medium stitch density embroidery patterns have been studied, satin fill and contour fill, implemented according to the ISO 4915:1991 301 stitch type standard. The impact and viability of these embroidery techniques over the dipole performance in cotton and felt textile substrates are reported. Test results confirm notable antenna parameter results in terms of return loss, radiation pattern, realized gain, and efficiency. In particular, contour pattern has been revealed as the best embroidery manufacturing technique in terms of quality factor and losses, whereas the satin pattern fits the resonance frequency of the antenna with a higher degree of accuracy.